Harnessing the biodiversity value of Central and Eastern European farmland. Issue 6 (18th December 2014) - Sutcliffe, Laura M. E.; Batáry, Péter; Kormann, Urs; Báldi, András; Dicks, Lynn V.; Herzon, Irina; Kleijn, David; Tryjanowski, Piotr; Apostolova, Iva; Arlettaz, Raphaël; Aunins, Ainars; Aviron, Stéphanie; et al.
Abstract A large proportion of European biodiversity today depends on habitat provided by low‐intensity farming practices, yet this resource is declining as European agriculture intensifies. Within the European Union, particularly the central and eastern new member states have retained relatively large areas of species‐rich farmland, but despite increased investment in nature conservation here in recent years, farmland biodiversity trends appear to be worsening. Although the high biodiversity value of Central and Eastern European farmland has long been reported, the amount of research in the international literature focused on farmland biodiversity in this region remains comparatively tiny, and measures within the EU Common Agricultural Policy are relatively poorly adapted to support it. In this opinion study, we argue that, 10 years after the accession of the first eastern EU new member states, the continued under‐representation of the low‐intensity farmland in Central and Eastern Europe in the international literature and EU policy is impeding the development of sound, evidence‐based conservation interventions. The biodiversity benefits for Europe of existing low‐intensity farmland, particularly in the central and eastern states, should be harnessed before they are lost. Instead of waiting for species‐rich farmland to further decline, targeted research and monitoring to create locally appropriate conservation strategies for these habitats is needed now.